Syngas production by chemical looping co-gasification of rice husk and coal using an iron-based oxygen carrier. (1st February 2022) - Luo, Ming; Zhang, Haiyan; Wang, Shuxiang; Cai, Jianjun; Qin, Yanjun; Zhou, Lunzheng
Highlights: The chemical looping co-gasification performance of rice husk and coal was studied. The synergistic effects between rice husk and coal were evaluated. Adding coal to rice husk could alleviate the ash deposition on oxygen carrier. Abstract: The chemical looping co-gasification (CLCG) of rice husk and coal using iron ore as an oxygen carrier was carried out in a fixed bed reactor. The effects of different parameters including oxygen/carbon ratio, reaction temperature, steam flow rate, and rice husk blending ratio on the gasification performance were studied. Based on the carbon conversion efficiency, gasification efficiency, and gas yield, the optimal conditions of the CLCG of rice husk and coal were determined. Moreover, the synergistic effect in carbon conversion and syngas production between those two fuels was also analyzed. The results showed that the carbon conversion efficiency, gasification efficiency, and gas yield reached 88.16%, 49.23%, 1.14 Nm 3 /kg, respectively at the oxygen/carbon ratio of 0.2, the reactor temperature of 900 °C, the steam flow rate of 0.125 g/min, and the rice husk blending ratio of 50%. At this condition, there were significant synergistic effects between rice husk and coal during the CLCG process, and the synergistic rate for carbon conversion efficiency and gasification efficiency reached 21.54% and 3.62%, respectively. The SEM-EDX analysis showed that adding coal to rice husk could alleviate the ash deposition phenomenon on the surfaces of iron ore during the CLCG process.